ARTIFICIAL INTELLIGENCE AND HUMAN THINKING - Jafar Mustafayev (Sciental Journals Publishing, 2025)
This article discusses the emergence, history, stages of development of artificial intelligence, the relationship between natural and artificial intelligence. It also describes the role and importance of artificial intelligence at the current level of development, and its relationship to human spiritual and moral censorship.
Keywords: Artificial intelligence, human intelligence, natural intelligence, computer revolution, information, security, cybernetics, neural systems.